Economic viability in the cultivation of different corn genotypes in second crop (Research, Society and Development, 2023)
The productive potential of corn is related to the genotype, which is responsible for part of the final yield due to the genetic potential, having a direct relationship with the soil and climate conditions of each location and the management adopted. Thus, the objective of this work was to evaluate the economic viability of corn second crop genotypes in a no-tillage system in the western region of Paraná. The experiment was installed in a randomized block design with seven maize genotypes, as follows; single hybrid, modified single hybrid, double hybrid, triple hybrid, variety, creole maize, homemade material 1 and homemade material 2 with four replicates at 0.45 m spacing. The production components of the crop were evaluated, with the exception of the mass of one thousand grains. Subsequently, the data were submitted to analysis of variance by the F test and later the means were submitted to comparison using the tukey test, by the SISVAR software. There was a difference between the treatments only in two variables, where the materials with the lowest genetic improvement had greater ear length and greater grain formation failure at the end of the ear. Although there is no statistical difference between the treatments for the final productivity, by the estimate performed, it is verified the importance of using certified and evolution materials regarding genetic improvement, where the use of the triple hybrid can be more advantageous to the rural producer. in this growing season based on the cost of obtaining the genotype and for obtaining the same productivity.